PENGUATAN KAPASITAS KELOMPOK WANITA TANI MELALUI DIVERSIFIKASI PRODUK OLAHAN PANGAN LOKAL - Suratna Suratna; Adi Soeprapto; Susanta Susanta; Simon Pulung Nugroho (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Hargomulyo Village is one of the villages in the Kokap Kulonprogo District of Yogyakarta which has high agricultural potential. Agricultural management efforts are mostly carried out by women. The Mekar Mandiri Women Farmers Group is a forum consisting of a group of farmer wives or female farmers in Hargomulyo Village who have activities in the agricultural sector in utilizing agricultural resources to work together to increase farm productivity and the welfare of its members. In carrying out its activities, the Mekar Mandiri Farmer Group has several obstacles: (1) Limited insight and skills in developing the potential of agricultural products into processed products with higher economic value; (2) Limited production equipment capable of processing agricultural products into processed products; (3) The low involvement of young people in the development of agricultural products. The solutions offered through these Community Service activities include: (1) training to broaden the horizons and increase the capacity of the community in managing local agricultural products-based processed products, (2) Facilitating the procurement of business equipment, (3) Assisting in applying for home industry permits and trademarks, and (4) Assistance in the manufacture of packaging designs for agricultural snack products. This Community Service activity is expected to increase the insight and capacity of the Mekar Mandiri Women's Farmer Group in processing agricultural products into processed products with higher economic added value.Arifin dan Biba, Arsyad, 2016, Pengantar Agribisnis, Mujahid Press, BandungBPS Kabupaten Kulonprogo, 2020, Produk Domestik Regional Bruto Kabupaten Kulonprogo Menurut Lapangan Usaha 2015-2019, Badan Pusat Statistik Kabupaten Kulonprogo, Kulonprogo.Craig, Gary, 2007, Capacity Building: Something Old, Something New..?, Critical Public Policy, 27(3):335-359Hermanu, Bambang, 2016, Implementasi Izin Edar Produk PIRT melalui Model Pengembangan Sistem Keamanan Pangan Terpadu, Prosiding Seminar Nasional Multi Disiplin Imu dan Call for Papers Unisbank (SENDI_U) ke-2, Unisbank Semarang, 425-435.Hudayana, Bambang,  Pande Made Kutanegara, Setiadi, Agus Indiyanto, Zamzam Fauzanafi, Mubarika Dyah F.N., Wiwik Sushartami, dan Mohamad Yusuf, (2019), Participatory Rural Appraisal (PRA) untuk Pengembangan Desa Wisata di Pedukuhan Pucung, Desa Wukirsari, Bantul, Bakti Budaya, 2(2):99-112Irrubai, Mohammad Liwa, 2015, Strategi Labeling, Packaging, dan Marketing Produk Hasil Industri Rumah Tangga di Kelurahan Monjok  Kecamatan Selaparang Kota Mataram Nus Tenggara Barat, Society Jurnal Jurusan Pendidikan IPS Ekonomi, Edisi XIII:15-30.Mukhtar, Syukrianti dan Nurif, Muchamad, 2015,  Peranan Packaging dalam Meningkatkan Hasil Produksi terhadap Konsumen, JSH : Jurnal Sosial Humaniora, 8(2):181-191 Mustanir, A, Hariyanti Hamid, Rifni Nikmat S, (2019), Pemberdayaan Kelompok Masyarakat Desa dalam Perencanaan Metode Partisipatif, Jurnal Moderat, 5(3):227-239Rahmadanih, Sitti Bulkis, Andi Amrullah, Rusli M.Rukka, M.Arsyad, (2015),  Strengthening Institutional Modelof Women-Farmers Group in Developing Household Food Diversification, International Journal of Agriculture System (IJAS), 3(1): 29-40Yuliana, Dina, (2017), Pemberdayaan Perempuan oleh Balai Penyuluhan Pertanian (BPP) melalui Kelompok Wanita Tani “Mekar Asri” di Dusun Mekar Mukti Desa Pasirmukti Kecamatan Cineam Kabupaten Tasikmalaya, Dinamika : Jurnal Ilmu Administrasi Negara, 4(3):417-423.